(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: every nation has its own traditions and customs. Daily life musical instruments, clothes, food products have a national color. That’s why many of us are interested in how they live in other countries. In this article you will learn what Japanese musical instruments are.